GLOBAL TRENDS IN PHARMACOGENOMICS INTEGRATION INTO CLINICAL PRACTICE: AN ARTICLE REVIEW - Nurul Magfirah Azis; Adi Priyono; Syahrul Tuba (Bajang Institute, 2026)
Introduction: The integration of pharmacogenomics into clinical practice offers great potential to transform conventional (trial-and-error) healthcare into preventive precision medicine, with the aim of minimizing treatment failure and adverse drug reactions. However, its global implementation still exhibits significant multidimensional disparities. Methods: This review article was compiled using a systematic narrative literature review of global scientific literature published through 2026 via the PubMed, Scopus, ScienceDirect, and Google Scholar databases. Results: Clinical standardization is dominated by international guidelines (CPIC and DPWG) as well as drug labeling policies from the FDA and EMA. Oncology is the most progressive sector in mandating pre-treatment genetic screening due to narrow therapeutic indices. Successful implementation in developed countries is supported by the digitization of genomic data integrated into Electronic Health Record (EHR) and Clinical Decision Support System (CDSS) systems. Nevertheless, adoption in developing countries remains hindered by high costs, limited insurance coverage, a lack of medical practitioner competency due to curriculum limitations, and the presence of a Caucasian population bias (genomic Eurocentrism) in global databases. Conclusion: Accelerating the widespread adoption of precision medicine requires a strategic shift from reactive testing to more cost-effective, preemptive preventive testing. Additionally, autonomous management of local genomic databases is necessary to eliminate ethnic bias, and interprofessional collaboration must be strengthened by positioning clinical pharmacists specializing in pharmacogenomics as key translational bridges to ensure patient safety.